The Relationship Between Emotion Regulation and Cyberbullying Behavior Among Students at SMKN 1 Kaidipang - Riska Riska; Anik Indarwati; Sri Ayu Mutmainah Kurniawati (Journal of Research in Social Science and Humanities, 2025)
This study aims to examine the relationship between emotion regulation and cyberbullying behavior among students at SMK Negeri 1 Kaidipang. Cyberbullying is a form of digital aggression that is prevalent among adolescents and is often triggered by negative emotions and poor emotional management skills. The research adopts a quantitative approach using a correlational survey method. The sample consisted of 37 students selected through purposive sampling. The research instruments included an emotion regulation scale based on Gross's theory and a cyberbullying behavior scale referring to aspects identified by Hinduja and Patchin. Data analysis using Pearson correlation revealed a significant negative relationship between emotion regulation and cyberbullying behavior (r = -0.483; p = 0.002). This indicates that the better students regulate their emotions, the lower their tendency to engage in cyberbullying.